THE DEVELOPMENT OF PEKA-BASED THINKING ACTIVITY WORKSHEET TO MEASURE THE STUDENTS’ THINKING SKILL - Guntara, Yudi; Pamungkas, Havid Noor (Unnes Science Education Journal, 2017)
Abstract ___________________________________________________________________ This research was aimed to develop PEKA-based thinking activity worksheet based, find out the feasibility of the worksheet, and determine the mastery level of thinking skill on the work and energy subject by using PEKA-based Thinking Activity worksheet. This type of research was research & development with 4-D model (Define, Design, Develop, and Disseminate). The initial product was validated by lecturers and teacher, and revised in the first revision. The revised worksheet was used in the limited testing then performed second revision. The final product was used in extensive trial. The results of this research shows that PEKA-based Thinking Activity worksheet is in good category with average score of 4.12. The level of student mastery in thinking skills was 55% at excellent, 36% at credit and 9% at satisfactory levels.